Environmental Monitoring of Water Quality in the Jangkok River, Mataram City - Muhammad Mardian Rizaldi; Tina Melinda (Jurnal Pijar MIPA, 2026)
The increase in population and domestic activities of the community along the banks of the Jangkok River contribute to the decline in river water quality. This study aims to analyze the water quality of the Jangkok River based on physical and biological parameters by comparing the measurement results to class III water quality standards according to PP No. 22 of 2021 and evaluate the water quality status using the Pollution Index according to the Decree of the Minister of Environment No. 115 of 2003. This type of research is Descriptive Quantitative. Sampling was conducted at three points upstream, downstream, and midstream and the samples were tested in the laboratory using Indonesian National Standard methods. The results show that the temperature in the upstream, middle and downstream sections is 26.3oC, the highest TSS value is in the upstream section, namely TSS 0.119 mg/L, the highest pH value is in the downstream section, namely 6.07, the highest DO value is in the upstream section, namely 19.78 mg/L, the highest BOD value is in the middle section, namely 4.48 mg/L, the highest COD value is in the downstream section, namely 84 mg/L and the lowest total coliform is in the upstream section, namely 91 MPN/ml. Several parameters, such as pH, DO, and COD, do not meet the class III quality standards under PP No. 22 of 2021, while temperature, TSS, BOD, and total coliform remain below these standards. The Pollution Index at all points is in the "lightly polluted" category, with IP values of 3.69 upstream, 3.68 in the middle, and 3.30 downstream. Domestic waste activities along the Jangkok River significantly impact water quality, although overall pollution levels remain relatively low. Waste management and public education are needed to maintain the river's sustainable function.